Direct RNA sequencing on nanopore arrays redefines the transcriptional complexity of a viral pathogen - Daniel P. Depledge (Nature Portfolio, 2019)
Here, Depledge et al. use nanopore arrays for direct RNA sequencing to profile the HSV-1 transcriptome in productively infected cells. Sequencing of individual RNAs reveals a highly complex viral transcriptome including mRNAs encoding new viral fusion proteins derived by read-through transcription.